2023
DOI: 10.2147/jaa.s364845
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Respiratory Viral Infections: A Spotlight on Climate Change and Air Pollution

Abstract: Climate change has both direct and indirect effects on human health, and some populations are more vulnerable to these effects than others. Viral respiratory infections are most common illnesses in humans, with estimated 17 billion incident infections globally in 2019. Anthropogenic drivers of climate change, chiefly the emission of greenhouse gases and toxic pollutants from burning of fossil fuels, and the consequential changes in temperature, precipitation, and frequency of extreme weather events have been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 113 publications
(144 reference statements)
0
5
0
1
Order By: Relevance
“…The highest increase was seen for PM 2.5 , a pollutant strongly associated with airway in ammation and childhood asthma [40,41]. In addition to the risk of asthma exacerbation, exposure to air pollution has also been linked to increased susceptibility to viral respiratory infections, including SARS-CoV-2 [42]. It is as such di cult to estimate the relative importance of different environmental factors in this study and we hypothesize that different factors contributed and interacted.…”
Section: Discussionmentioning
confidence: 87%
“…The highest increase was seen for PM 2.5 , a pollutant strongly associated with airway in ammation and childhood asthma [40,41]. In addition to the risk of asthma exacerbation, exposure to air pollution has also been linked to increased susceptibility to viral respiratory infections, including SARS-CoV-2 [42]. It is as such di cult to estimate the relative importance of different environmental factors in this study and we hypothesize that different factors contributed and interacted.…”
Section: Discussionmentioning
confidence: 87%
“…If weather is less relevant to circulation than previously believed, some surges (in very young infants or immunocompromized groups) should be expected more frequently throughout the year. Furthermore, as summer peaks are clearly possible for some of them, global changes in weather might alter viral dynamics in ways that are difficult to predict, which is particularly relevant in the context of climate change [ 77 , 78 ]. Further analysis on the effects of weather and behaviour on NIRVs is in order, both in laboratory and epidemiological settings, to inform models and allow simulation of different complex scenarios and interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemics involving viral RTIs have always vary in regional intensity and duration -This is thought to be due to the genetic diversity of circulating viruses and their respective virulence. Climatic changes also seem to impact on virus spread (7,19,20). Numerous studies have shown that NPIs reduce the circulation of SARS-CoV-2 and other respiratory pathogens (21).…”
Section: Discussionmentioning
confidence: 99%